Le webdocumentaire : une opportunité pédagogique pour l’éducation critique aux médias ? - Muriel BEASSE; Najoua MOHIB (Tic & Société)
This article seeks to explore the potential contribution of web documentaries towards critical thinking in media education in the digital era. Our analysis is based on a survey of learner appropriation of this medium, which has been the focus of few didactic experimentations despite fifteen years of existence. More than a digital tool, web documentaries are an editorial genre, a locust of constant innovation which make full use of the multiple affordances of new digital media. Our findings show their potential didactic value along with the skills they can develop.